Disarmament. Review of the acts of the League of Nations and of Government, parliamentary debates and the trend of public opinion relating to the World disarmament conference, 1932. Publ. by the Disarmament information Committee at Geneva
French ed.: Désarmement. Revue ... (ZK 29010) - German ed.: Abrüstung. Zeitschrift ... (ZK 29002).